Bandwidth expanding technology for dynamic crosstalk aware single-walled and multi-walled carbon nanotube bundle interconnects. (August 2018) - Zhao, Songjie; Pan, Zhongliang
Abstract: In view of scarce bandwidth resources, an inductive peaking technology is used to expand 3-dB bandwidth of the coupled single-walled and multi-walled carbon nanotube bundle interconnects, which take the dynamic crosstalk into account. Based on decoupling technique and ABCD parameter matrix approach, the transfer function of the decoupled victim line at global level of 14 nm technology node is derived to analyze and compare the bandwidth performance under different length, diameter, temperature and load resistance conditions. It is obvious that 3-dB bandwidth can be effectively expanded by adding peaking inductance to the load irrespective of phase-mode. However, the bandwidth will remain nearly unchanged once the adding inductance reaches a certain extent. Furthermore, the overshoot and undershoot in the step response will be caused with the further increase of the peaking inductance. On the other hand, it is shown that the value of 3-dB bandwidth at out-of-phase mode is much smaller than that at in-phase mode under the same condition.